James Gillray’s The Shrine at St Ann’s Hill and the Rights of Man - Christensen, Jørgen Riber (Academic Quarter | Akademisk kvarter, 2012)
James Gillray’s satirical etching from 1798 is both a comment on the French Revolution and on the political reaction to it in England. It is significant that Gillray’s opposition to the French Revolution here takes the form of an attack on the Declaration of the Rights of Man and of the Citizen (Déclaration des droits de l´homme et du citoyen, which are depicted as anything but humane. It is the aim of the article to explore the genesis of human rights in the context of both the French Revolution and outside France in Britain. The point of departure of this investigation is the aesthetics of Gillray´s etching.